Freud e o envelhecimento: a importância da compreensão psicodinâmica do idoso - Saraiva Junior, José Ribamar Fernandes (2017)
According to Freud, each one grows old in his own way. Considering the uniqueness of each old age is fundamental to conceive that elderly will use their future in a unique way to treat real from unconscious. For this, present work tries to describe, from revision of published works of Freud, the relation between psychoanalysis and aging. It seeks to identify what Freudian theory can contribute to the universe of the elderly, for a better understanding of human aging. Identify which points of Freud's vision can be used as a reference for understanding elderly and maintaining health of geriatric patient. This article intends to enlarge the theme about Freud's writings on aging and about psychoanalysis of aging, contributing to understanding of elderly in contemporary world and their correlation with current psychoanalysis. The method used to produce this work was the complete revision of Brazilian standard edition of the complete works of Sigmund Freud published in 1996. In analyzing Freud's complete work, it can be perceived, throughout his studies on the human mind, a gradual change in his conceptions of old age, aging, and elderly. This important work of psychoanalysis has brought contributions to human development and family relationships, so important for healthy aging.